2022
DOI: 10.1001/jamasurg.2022.0297
|View full text |Cite
|
Sign up to set email alerts
|

Comments on Surgeon-Patient Sex Concordance and Postoperative Outcomes—Reply

Abstract: In Reply As Bai et al note, general surgery has historically been a (White, cisgendered, heterosexual) male-dominated field. Our data indicate lack of inclusion is experienced by many with minoritized identities in surgery, including lesbian, gay, bisexual, transgender, queer, and other sexual and gender minority (LGBTQ+) physicians. We agree that this lack of inclusion likely leads LGBTQ+ residents to withhold their identity. In our survey of 85.6% of all residents training in accredited general surgery progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 6 publications
2
20
0
2
Order By: Relevance
“…Two recent studies have confirmed that women surgeons performed better surgery and had a lower incidence of adverse reactions after surgery than men surgeons. [28,29] So we can speculated that women gastroenterologists might do a better job than men, have more favorable patient outcomes. Therefore, our study is likely to encourage more women to engage in work related to H. pylori and help them get more academic opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have confirmed that women surgeons performed better surgery and had a lower incidence of adverse reactions after surgery than men surgeons. [28,29] So we can speculated that women gastroenterologists might do a better job than men, have more favorable patient outcomes. Therefore, our study is likely to encourage more women to engage in work related to H. pylori and help them get more academic opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…14 This should be taken as a learning point for male and female urologists on the importance of empathy and open communication to ensure a healthy physician–patient relationship and appropriate care. Interestingly, a recent publication in JAMA Surgery 15 showed that discordant gender between surgeon and patient resulted in adverse patient outcomes, with the most significant trend seen between male surgeons with female patients. Whereas no direct causative factors were explored in the study, the findings are concerning.…”
Section: Discussionmentioning
confidence: 99%
“…Female surgeons have been shown to have lower postoperative complications and mortality than male surgeons and although the reasons for this are difficult to pinpoint, it provides further incentive to correct the gender imbalance within surgery. 12 13…”
Section: Introductionmentioning
confidence: 99%